Integrated management of faba bean chocolate spot caused by Botrytis fabae in Gondar, Ethiopia. (15th June 2018) - Sahile, Samuel Woldemariam; Teshome, Zewdu; Kibret, Mulugeta
Abstract: Integrated management of faba bean chocolate spot ( Botrytis fabae Sard.) was studied using moderately tolerant variety, "Hachalu" and the local cultivar at Chilga district during 2016 main cropping season. The objective was to evaluate effect of host resistance, intercropping and fungicide applications on epidemics of faba bean chocolate spot, yield and yield components of faba bean, and sole and intercrop systems productivity. The experiment was randomised complete block design in a factorial combination of two faba bean cultivars, two cropping systems (Hachalu- and local-barley intercropping in 2:1 ratio) and four levels of fungicide (Chlorothalonil) spray and integration in three replications of faba bean and barley, respectively. Cultivars and spray intervals significantly ( p < .01) affected the seed yield while cultivars alone had significant variation ( p < .01) on 100-seed weight as a main effect. Therefore, 21-days fungicide spray intervals integrated with Hachalu sole and Hachalu-barley intercropping may be considered for chocolate spot management.